2019
DOI: 10.1111/jace.16265
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐induced phase transitions in PZxBMN binary solid solutions

Abstract: Solid solutions of (1−x)PbZrO 3 -xBa(Mg 1/3 Nb 2/3 )O 3 (PZ-xBMN, x = 0.02, 0.03, 0.04, and 0.05) were prepared, and their microstructures, electrical properties, and phase transition behaviors under hydrostatic pressure were investigated. It was found that the incorporation of BMN into PZ can provide improved ferroelectric properties, leading to the formation of antiferroelectric/ferroelectric phase boundaries in PZ-xBMN ceramics when the value of x is between 0.02 and 0.03. It was also demonstrated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Many studies have been devoted to addressing this issue of PZT95/5 and improving its temperature stability via the introduction of La 3+ , Sn 4+ , Ba 2+ , and so on. Among them, the introduction of Ba(Mg 1/3 Nb 2/3 )O 3 to PbZrO 3 to build a new solid solution of PbZrO 3 -Ba(Mg 1/3 Nb 2/3 )O 3 (PZ-BMN) ceramics completely eliminated the temperature-induced FE LTR-HTR phase transformation with a minor loss of P r up to 125 • C. 116,117 However, its phase structure evolution under hydrostatic pressure, discharge behavior under shock waves, and failure mechanism still need to be comprehensively studied to satisfy conditions for actual application.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…Many studies have been devoted to addressing this issue of PZT95/5 and improving its temperature stability via the introduction of La 3+ , Sn 4+ , Ba 2+ , and so on. Among them, the introduction of Ba(Mg 1/3 Nb 2/3 )O 3 to PbZrO 3 to build a new solid solution of PbZrO 3 -Ba(Mg 1/3 Nb 2/3 )O 3 (PZ-BMN) ceramics completely eliminated the temperature-induced FE LTR-HTR phase transformation with a minor loss of P r up to 125 • C. 116,117 However, its phase structure evolution under hydrostatic pressure, discharge behavior under shock waves, and failure mechanism still need to be comprehensively studied to satisfy conditions for actual application.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…Piezoelectric material has been widely applied in numerous electromechanical devices. In fact, piezoelectric material usually works under mechanical pressures [1], thus, some researchers concentrate on the effects of mechanical pressures on piezoelectric material [2][3][4][5][6][7]. For example, Yao et al reported that the piezoelectric coefficient decreases with increasing the mechanical pressures in the PbTiO 3 -based piezoelectric ceramic, which was further explained by the pressure-induced depolarization [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yao et al reported that the piezoelectric coefficient decreases with increasing the mechanical pressures in the PbTiO 3 -based piezoelectric ceramic, which was further explained by the pressure-induced depolarization [4]. Pressure induced phase transformations are also reported widely [5][6][7][8][9]. Hall et al suggested a phase transformation from the rhombohedral to the orthorhombic phase within the PbZrO 3 -PbTiO 3 piezoelectric ceramic, induced by pressure [3].…”
Section: Introductionmentioning
confidence: 99%